The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3892/etm.2022.11262
|View full text |Cite
|
Sign up to set email alerts
|

Frozen blastocysts: Assessing the importance of day 5/day 6 blastocysts or blastocyst quality

Abstract: The aim of the present study was to analyze the high-quality blastocyst (HB) rate in all embryo frozen cycles and investigate the pregnancy outcomes for day 5/day 6 (D5/D6) blastocysts with respect to the blastocyst quality in programmed single vitrified-warmed blastocyst transfer (SVBT). We performed a retrospective study comparing D5/D6 HBs in in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) for all blastocyst frozen cycles. Patients were <35 years at the oocyte collection in their first fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
12
0
2
Order By: Relevance
“…Recently, retrospective cohort studies concluded that the clinical pregnancy, implantation, and LBR after frozen-thawed blastocyst transfer are significantly higher in D5 embryos than in D6 embryos [ 9 , 10 ]. However, some studies found no significant difference between day 5 and day 6 frozen-thawed blastocysts, with similar clinical pregnancy, implantation, and birth rates [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, retrospective cohort studies concluded that the clinical pregnancy, implantation, and LBR after frozen-thawed blastocyst transfer are significantly higher in D5 embryos than in D6 embryos [ 9 , 10 ]. However, some studies found no significant difference between day 5 and day 6 frozen-thawed blastocysts, with similar clinical pregnancy, implantation, and birth rates [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The blastocyst was then moved at room temperature (22–25 °C) to Kitazato (Japan) equilibration solution (ES). After 6–8 min, the blastocyst was quickly washed in vitrification solution (VS) for 45–60 s and transferred onto the straw (Kitazato Japan) using a micropipette and immersed vertically into liquid nitrogen [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…After 1 or 2 h of culture the embryo was reassessed again and often the re-expansion of the blastocoel was reported; this indicated that the embryo physiologically survived the warming procedure. Embryo transfer was normally performed within 2 or 3 h. All programmed warmed cycles, both at D5 and D6, were transferred in D5 endometrium [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The blastocyst was then moved at room temperature (22-25°C) to Kitazato (Japan) equilibration solution (ES). After 6-8 min, the blastocyst was quickly washed in vitri cation solution (VS) for 45-60s and transferred onto the straw (Kitazato Japan) using a micropipette and immersed vertically into liquid nitrogen (Jiang et al 2022).…”
Section: Blastocyst Vitri Cation and Warming Proceduresmentioning
confidence: 99%
“…Clinical outcome B ultrasound was used to observe the gestational sac and fetal heart at 35 days after implantation was diagnosed as clinical pregnancy. Implantation rate was de ned as the ratio of the number of gestational sacs and fetal heart observed under B ultrasound and the number of transferred embryos (Jiang et al 2022). The clinical pregnancy rate, implantation rate, ectopic pregnancy, abortion rate and live birth rate were analyzed.…”
Section: Clinical Outcomementioning
confidence: 99%